SHARP HAUSDORFF YOUNG INEQUALITY AND INVERSION FORMULA FOR THE COUPLED WINDOWED OFFSET FRACTIONAL FOURIER TRANSFORM - Nasrullah Bachtiar; Erica Grace Simanjuntak; Nora Madonna (Jurnal Matematika UNAND, 2026)
This work presents the Sharp Hausdorff-Young inequality for the Coupled windowed offset fractional Fourier transform. The coupled windowed offset fractional Fourier transform can be regarded as a generalized version of the fractional windowed Fourier transform. Various properties, including an inversion formula, are studied in detail for the coupled windowed offset fractional Fourier transform. Additionally, relationships with both the two-dimensional Fourier transform and the two-dimensional coupled windowed fractional Fourier transform are also studied.